2011
DOI: 10.1021/jp204856c
|View full text |Cite
|
Sign up to set email alerts
|

Graphite Oxide with Different Oxygenated Levels for Hydrogen and Oxygen Production from Water under Illumination: The Band Positions of Graphite Oxide

Abstract: Graphite oxide (GO) photocatalysts derived from graphite oxidation can have varied electronic properties by varying the oxidation level. Absorption spectroscopy shows the increasing band gap of GO with the oxygen content. Electrochemical analysis along with the Mott–Schottky equation show that the conduction and valence band edge levels of GO from appropriate oxidation are suitable for both the reduction and the oxidation of water. The conduction band edge shows little variation with the oxidation level, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
169
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 272 publications
(179 citation statements)
references
References 78 publications
9
169
0
1
Order By: Relevance
“…The stable evolution of hydrogen even at low band gap energy not only suggests that the CB of semiconducting GO is laid down at a suitable energy state corresponding to H + /H 2 potential but also indicates that the transitional decay in the GO band gap is attributed to the upward shift of the VB, which is responsible for the lack of O 2 evolution, even in the presence of a scavenging Ag + ion [50]. This hypothesis can be extracted from the spectroscopic measurements, indicating that the removal of oxygen-containing groups on the surface leads to the reduction in the band gap through shifting the VB maximum upward, while the CB potential remained nearly unchanged at −0.75 to −0.71 eV versus Ag/AgCl [51,52]. Further oxidization of GO increases the band gap and provides sufficient overpotential at the GO molecular orbital for an O 2 evolution reaction.…”
Section: Graphene As Photocatalystmentioning
confidence: 90%
See 1 more Smart Citation
“…The stable evolution of hydrogen even at low band gap energy not only suggests that the CB of semiconducting GO is laid down at a suitable energy state corresponding to H + /H 2 potential but also indicates that the transitional decay in the GO band gap is attributed to the upward shift of the VB, which is responsible for the lack of O 2 evolution, even in the presence of a scavenging Ag + ion [50]. This hypothesis can be extracted from the spectroscopic measurements, indicating that the removal of oxygen-containing groups on the surface leads to the reduction in the band gap through shifting the VB maximum upward, while the CB potential remained nearly unchanged at −0.75 to −0.71 eV versus Ag/AgCl [51,52]. Further oxidization of GO increases the band gap and provides sufficient overpotential at the GO molecular orbital for an O 2 evolution reaction.…”
Section: Graphene As Photocatalystmentioning
confidence: 90%
“…Further oxidization of GO increases the band gap and provides sufficient overpotential at the GO molecular orbital for an O 2 evolution reaction. However, the activity of the photocatalyst is expected to decline via photo-reduction, as shown for GO before and after photo reduction in Figure 5a and b, respectively [51].…”
Section: Graphene As Photocatalystmentioning
confidence: 97%
“…Teng group [104] first proved that RGO with the bandgap of 2.4-4.3 eV exhibited stable H 2 evolution from an aqueous methanol solution or pure water, even without Pt cocatalyst under irradiation with light from a mercury light lamp. They also investigated the photocatalytic activity of RGO at various oxidation levels, and found that there was an inverse relationship between the photocatalytic activity and the amount of the oxygen-containing groups on the RGO sheets [105]. However, an unexpected phenomenon was that the O 2 evolution exhibited a decreasing trend, although the H 2 -evolution rate of RGO was stable over time.…”
Section: Graphene-based Mixed-colloid Photocatalytic Systemsmentioning
confidence: 99%
“…5.1). Afterwards, they investigated the photocatalytic activity of GO at various oxidation levels and established an inverse relationship between the amount of H 2 evolution and the population of the oxygen-containing groups on the GO sheets [5]. They concluded that the GO sheets with higher oxidation degree have a larger band gap and limited absorption of light, thus exhibiting a lower photocatalytic activity than the GO sheets with lower oxidation degree.…”
Section: Application Of Go In Energy Conversion and Storagementioning
confidence: 99%